2015
DOI: 10.1016/j.clinthera.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Brain MRI Characteristics and Postoperative Delirium in Cardiac Surgery Patients

Abstract: Purpose Delirium is common after cardiac surgery, and it is associated with short- and long-term consequences, including cognitive decline. Identification of patients who are vulnerable to delirium might allow for early implementation of delirium-prevention strategies in older adults undergoing surgery. Brain MRI findings provide insight into structural brain changes that may identify vulnerable patients. The purpose of this study was to examine the association between brain MRI characteristics potentially ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 44 publications
1
31
1
1
Order By: Relevance
“…Two recent MRI studies could show neither a significant association between brain atrophy or whitematter hyperintensities (Cavallari et al 2015), nor between global or voxel-wise cerebral blood flow, with the incidence and severity of postoperative delirium (Hshieh et al 2016) in nondemented elderly patients. These findings contrast with previous assumptions about neuroradiological risk factors for delirium (Brown et al 2015, Soiza et al 2008). In another study, the correlations of blood oxygen levels between various brain regions in resting-state fMRI scans of patients both during the acute episode and after its resolution were examined (Choi et al 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Two recent MRI studies could show neither a significant association between brain atrophy or whitematter hyperintensities (Cavallari et al 2015), nor between global or voxel-wise cerebral blood flow, with the incidence and severity of postoperative delirium (Hshieh et al 2016) in nondemented elderly patients. These findings contrast with previous assumptions about neuroradiological risk factors for delirium (Brown et al 2015, Soiza et al 2008). In another study, the correlations of blood oxygen levels between various brain regions in resting-state fMRI scans of patients both during the acute episode and after its resolution were examined (Choi et al 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…ApoE4, a marker of Alzheimer's disease, was no risk factor in surgical patients [31,32]. One study group found brain atrophy not to be associated with incidence of POD [33], whereas others identified decreased grey matter volume or cerebral atrophy contributing to POD [34,35].…”
Section: Psychomotoric Subtypes Of Deliriummentioning
confidence: 94%
“…Another study assessed WMHs after cardiothoracic surgery and demonstrated a trend towards association with post‐operative delirium ( N = 79; WMH 10‐point scale: 3 vs. 2; p = 0.05; Brown et al, ).…”
Section: Structural Neuroimagingmentioning
confidence: 99%
“…Five studies assessed the relationship between cerebral atrophy and delirium involving 846 patients of whom 175 had delirium. One study (Brown et al, ) used a validated 10‐point rating scale for assessment of cerebral ventricular size and sulcal widening (Manolio et al, ). A validated stroke‐specific 4‐point visual scale (Pasquier et al, ) grading regional sulcal and ventricular atrophy was used in another study (Oldenbeuving et al, ).…”
Section: Structural Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation